Five go off to camp. 7 - Blyton, Enid; Soper, Eileen Alice (Hodder Children's London, 1997)
"Spook-trains in the dead of night! They seem to vanish into thin air -- where do they go? The Famous Five follow the tracks -- and discover a very unusual, underground destination!"--Page 4 of cover